Science and subjectivity - Scheffer, Israel (Indianapolis Hackett Publishing company, 1982)
" . . . a standard source for anyone wanting to immerse himself in the topic of scientific change, Kuhn, Feyerabend, Hanson and Polanyi, all are examined here in a manner which is at once sympathetic and exacting." -- Roger C Buck, Indiana University